2021
DOI: 10.3390/cancers13194945
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry Immunophenotyping for Diagnostic Orientation and Classification of Pediatric Cancer Based on the EuroFlow Solid Tumor Orientation Tube (STOT)

Abstract: Early diagnosis of pediatric cancer is key for adequate patient management and improved outcome. Although multiparameter flow cytometry (MFC) has proven of great utility in the diagnosis and classification of hematologic malignancies, its application to non-hematopoietic pediatric tumors remains limited. Here we designed and prospectively validated a new single eight-color antibody combination—solid tumor orientation tube, STOT—for diagnostic screening of pediatric cancer by MFC. A total of 476 samples (139 tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
1
9
0
1
Order By: Relevance
“…Combining CC and flow cytometry a high diagnosis yield (81/96) was reached avoiding more invasive procedures. As previously reported (Béné et al, 2016;Ferreira-Facio et al, 2021;Gautam et al, 2008), this was not limited to small round cell tumors, but also in other tumors, such as ADC or SCC. FNA biopsy results can also be useful to establish an initial diagnosis or indicate the need to obtain additional samples (Leon et al, 2004).…”
Section: Evaluation Of Immune Cell Populations In Infiltrated Versus ...supporting
confidence: 76%
See 2 more Smart Citations
“…Combining CC and flow cytometry a high diagnosis yield (81/96) was reached avoiding more invasive procedures. As previously reported (Béné et al, 2016;Ferreira-Facio et al, 2021;Gautam et al, 2008), this was not limited to small round cell tumors, but also in other tumors, such as ADC or SCC. FNA biopsy results can also be useful to establish an initial diagnosis or indicate the need to obtain additional samples (Leon et al, 2004).…”
Section: Evaluation Of Immune Cell Populations In Infiltrated Versus ...supporting
confidence: 76%
“…MFC has a well-established role in the diagnosis, prognosis and follow up of hematolymphoid neoplasms and is successfully performed in peripheral blood, BM, body fluids, and tissue samples (Béné et al, 2016). Out of this context, MFC has been introduced in cancer research (Davidson et al, 2007;Davidson et al, 2012) but few studies are devoted to clinical applications for detection of malignant cells (Acosta et al, 2016;Ferreira-Facio et al, 2013;Ferreira-Facio et al, 2021;Gautam et al, 2008;Wong-Arteta et al, 2020).…”
Section: Antigen Expression and Sclc Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Ключевым отличием бластов при ОЛ является экспрессия линейно-специфических антигенов, в то время как при солидных опухолях кроме отсутствия общелейкоцитарного антигена CD45 наблюдается экспрессия только неспецифических маркеров, встречающихся на гемопоэтических клетках (CD56, CD81, CD9, CD99 и др.) [12][13][14][15][16]. При выявлении в КМ только гемопоэтических клеток в ряде случаев может быть также актуальным вопрос подтверждения опухолевой природы выявленных в образце клеток-предшественников (особенно при их малом количестве).…”
Section: алгоритм проведения анализаunclassified
“…It is mainly due to the need to obtain (fresh) suspensions of individual cells and that, unlike IHC, MFC does not provide information on the structure and location of tumor cells in tissues [7]. Therefore, early studies on the use of MFC in solid tumors mainly focused on detecting disseminated disease in the bone marrow [8,9]. Those studies revealed different antigen expression profiles among metastatic non-hematopoietic bone marrow tumor cells.…”
Section: Diagnosticsmentioning
confidence: 99%